Transformation of dolomite powder into value added fertilizer and its effect on growth and yield of tomato plant - Parmar, Divya; Meenakshi, (Comunicata Scientiae, 2024)
In Dolomite industry, various purposes have led to the generation of large amount of dolomite powder during mechanical processing. Dolomite is a rich source of Ca and Mg and XRF analysis showed the presence of certain micro and ultra micro plant nutrients in it. In the raw form these nutrients are not in easily plant accessible form. In the present research, dolomite powder was converted into easily plant accessible form and its value-added fertilizer is formed by mixing vermicompost with chemically converted dolomite powder. Three types of experiments- control (simple soil), control with compost (soil + vermicompost), and different percentages [X, 2X, 3X, 4X & 5X (X= 3%)] of value-added fertilizer with soil were performed on growth and yield of tomato plant. It was found that among all treatments, 5X showed maximum plant growth, crop yield with increased biomass.